Design of A Flexible Liquid Metal Tactile Sensor Based on Finite Element Analysis for Pressure and Motion Detection - Zhou Zhao; Xiaoyang Zou; Jing Zhang; King Wai Chiu Lai (Advanced Electronic Materials)
Abstract Liquid metals (LMs) have emerged as prominent materials for flexible pressure sensing owing to their exceptional conductivity and fluidity. Typically, external loads induce changes in the shape and volume of conductive LM pathways to achieve pressure detection. To optimize sensor's pressure sensitivity, theoretical modeling and finite element simulations are employed to investigate the effects of microchannel thickness and patterns. Results revealed that symmetrical patterns and thinner microchannels significantly enhanced sensor's pressure sensitivity. Furthermore, a novel polyvinyl alcohol (PVA) sacrificial template method is proposed that enables the flexible fabrication of microchannels with various shapes and thicknesses, achieving a minimum channel thickness of 25 µm. The LM sensor demonstrates excellent performance metrics, including a maximum sensitivity of 0.01212 kPa−1, a wide detection range from 0 to 60 kPa, and remarkable cyclic stability up to 3000 cycles. In practical applications, the sensor enables high‐precision monitoring of various human movements, whereas sensor arrays can effectively detect force distributions across different objects. This paper presents a straightforward and efficient approach for regulating and designing conductive microchannel paths. Additionally, the integration of finite element simulations facilitates optimal sensor pattern design, and the fabricated sensors show tremendous potential for applications in pressure recognition and motion detection.